Multiple cerebral venous thrombosis after endoscopic stapedotomy: A potential role of endoscope-produced heat. Issue 1 (1st January 2017) - Salzman, Richard; Stárek, Ivo; Heřman, Jan
Abstract: Authors present the very first case of cerebral venous thrombosis (CVT) after endoscopic stapedotomy. A 37-year-old female underwent routine endoscopic stapedotomy using 18-cm long 30° endoscope with 2.7-mm diameter, attached to Storz Power LED light source with 60% intensity. On day 5, she returned with vertigo, tinnitus without any sign of inflammation. After a slight improvement, she started to complain about left hand paresis. The magnetic resonance angiography showed venous thrombosis of superior sagittal, right transverse and right sigmoid sinuses, and thrombosis of central veins. The patient received full anticoagulation therapy. Six months later, imaging confirmed complete recanalization of all cranial sinuses. She has fully restored her mobility. She is only left with moderate right-sided senso-neural hearing loss and tinnitus. The authors hypothesize that the exposure to steadily held endoscope resulted in higher amount of heat spreading within the middle ear cleft that could have caused a small middle ear venule thrombosis which further spread to cerebral sinuses in the high-risk patient of spontaneous CVT due to her smoking and oral contraceptives use. A temperature of 104 °C can be measured at the tip of a "cold" light endoscope. The direct thermal tissue damage is induced when the temperature rises above 50 °C. Even smaller temperature elevation can, however, irritate vestibular functions. More studies looking at heat production and subsequent complications in endoscopic ear surgery are necessary. For now, we suggest detailed description of type and intensity of light source to be included in all papers on endoscopic ear surgeries.